Estados Unidos y la transformación general de las empresas españolas - García Ruiz, José Luis (Cuadernos de Historia Contemporánea, 2003)
Business administration was implemented in the United States during the last decades of the 19th century, much earlier than in Europe. Soon afterwards it was identified as a key factor in the American progress to world leadership and a debate on the possibilities of the Americanization of the business structures outside the United States was open. During the first half of the 20th century, it was not possible to go ahead in this way in the Spanish case because of the huge differences between the two countries. But, as it is shown in this work, there were also many difficulties during the fast growth years of the 1960s and afterwards. Culture seems to have played an important role in these resistances.